Design And Development Of Chopper Machine For Palm Oil Midrib - Arif, Muhammad; Azmi, Azmi; Purba, Immanuel (Kopertis Wilayah X)
The midrib of palm oil has good potency to be processed become animal feed (silage) and compost where the midribs are chopped into small pieces. The opportunity of this development process that can more be benefit and valuable encourages researcher to design and create a machine that capable to chop the midribs of palm oil. In this research, researcher designs and creates a chopper machine which can be operated safely and more efficient based on ergonomics approach. Researcher also uses anthropometry method with 30 samples and collecting creative ideas through brainstorming to produce a best design. The chopper machine has certain dimension determined by anthropometri data calculation through test data sufficiency, uniformity test data and calculation of percentil and had been obtained 107.85 cm for height, 120 cm for length and 58 cm for width. The chopper machine also uses 4 blades and working based on clockwise direction.